Analisis Biayariil Dan Kesesuaian Dengan Tarif INA-CBG’S Pada Pasien Kanker Kolorektal Di RSUD Dr. Moewardi Surakarta Tahun 2018 - Annora Rizky Amalia (Fakultas Farmasi Universitas Setia Budi, 2021)
Colorectal cancer is cancer that starts from the colon or rectum. Colorectal cancer occurs when tumors form in the lining of the large intestine. The high real cost of colorectal cancer chemotherapy is a major factor in creating a national health insurance program through the INA-CBG package. The purpose of this study was to determine the suitability of real costs with INA-CBG package rates and factors that affect real costs in colorectal cancer patients hospitalized in Dr. Moewardi Surakarta. This study uses observational cross-sectional methods. Data taken retrospectively. The subjects of this study were colorectal cancer patients who were hospitalized at Dr. Moewardi Surakarta in 2018. Subjects and objects of this study were colorectal cancer chemotherapy patients who hospitalization and medical record data and inpatient claim service files at Dr. Moewardi general hospital of Surakarta for the period of January - December 2017. The analysis used is one-sample t-test to determine the suitability between real costs and INA-CBG rates and bivariate correlation analysis to determine the relationship of real costs with factors that affect real costs. The results showed the complex intestinal procedure (K-1-20-I / II / III) had an average cost that was higher than the other procedures which was Rp. 20,889,414.64. This relates to the increase in costs for medical treatment and also pharmaceutical costs. Based on the magnitude of the difference between the real rates with the INA-CBG package in colorectal cancer patients in Dr. Moewardi Surakarta in 2018 the procedure that has the highest cost difference in chemotherapy procedures at the severity of C-4-13-I with a total difference of Rp - 671,021,073,14 (negative difference). The most influential factor is Length of Stay (LOS) in anal procedures with INA-CBG's K-1-50 code with a value of p <0.05 (0,000) and in digestive tumor procedures with INA-CBG's K-4-10 code with p-value <0.05 (0.001).